Preparation method of single-layer molybdenum disulfide catalyst, prepared catalyst and application
By using dual-template technology to prepare a single-layer molybdenum disulfide catalyst under normal pressure, the problem of easy deactivation of traditional catalysts at high temperatures is solved, and a catalytic effect with high activity and high stability is achieved, which is suitable for reverse-hydraulic gas transformation reactions.
Patent Information
- Application Number
- CN202411825253.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
AI Technical Summary
The traditional counterhydraulic gas transformation reaction catalyst is prone to deactivate at high temperatures, and the noble metal catalyst is insufficient in the presence of trace sulfides, which affects the industrialization process of the reaction.
The monolayer molybdenum disulfide catalyst was prepared by combining silica and surfactant dual-template plates under normal pressure by reducing hydrazine hydrate under normal pressure. The thermal stability and specific surface area of the catalyst were improved through silicon sphere dispersion and surfactant intercalation technology.
The prepared monolayer molybdenum disulfide catalyst maintained structural stability in the 600°C test, with higher anti-hydraulic gas transformation reaction activity and stability, and the selectivity of CO remained above 99%.
Smart Images

Figure CN119797429A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a monolayer molybdenum disulfide catalyst, the prepared catalyst and its application, and belongs to the field of chemistry and chemical engineering. Background Art
[0002] In recent years, the global economy has grown rapidly, and the demand for energy in modern society has continued to increase. With the extensive use of fossil energy, the concentration of CO2 in the atmosphere has continued to increase, and the climate and environmental problems caused by this have continued to intensify. Therefore, vigorously promoting the chemical conversion of CO2 is an effective means to reduce global carbon emissions. The reverse water gas shift reaction (RWGS) uses "green hydrogen" produced by renewable energy such as solar energy and wind energy to catalytically convert the captured and recovered CO2 into synthesis gas (CO+H2), and then synthesize high-value-added oil products through the Fischer-Tropsch reaction process, which is conducive to improving the energy structure, reducing the consumption of fossil energy, and realizing the effective circulation of carbon resources.
[0003] The reverse water gas shift reaction is a traditional endothermic reaction (ΔH 298K =41.1 kJ mol -1 ), high temperature is conducive to the reaction process, so there are higher requirements for the high temperature stability of the catalyst, and in order to reduce the subsequent separation cost, the occurrence of side reactions must be avoided as much as possible. The traditional reverse water gas shift reaction generally uses non-precious metal copper-based, iron-based metal / metal oxide catalysts or precious metal platinum-based catalysts (Journal of energy chemistry, 2017, 26 (5): 854-867.). Due to the low Tamman temperature of active metal copper and iron, sintering is easy to occur during the reaction, causing grain growth and thus catalyst deactivation. Precious metal catalysts are prone to produce methane as a byproduct due to their strong hydrogenation activity, and the stability of precious metal catalysts also limits their application due to the presence of trace sulfides in the reaction. The existence of these problems has seriously affected the industrialization process of the RWGS reaction. Therefore, the development of a catalyst that is efficient and stable at high temperatures is of great significance for reducing carbon emissions.
[0004] In recent years, many research results have shown that molybdenum disulfide exhibits excellent catalytic activity in the hydrogenation reaction of carbon dioxide (International Journal of Hydrogen Energy, 2024, 68: 35-50.). As a typical two-dimensional transition metal sulfide, molybdenum disulfide has good thermal stability and sulfur resistance. Li et al. used theoretical calculations to prove that sulfur vacancies are the main catalytic active centers of CO2 hydrogenation reactions during CO2 hydrogenation reactions (Applied Surface Science, 2023, 635: 157721.). Deng et al. prepared molybdenum disulfide with different numbers of layers and proved that the reduction in the number of layers can effectively increase the concentration of sulfur vacancies and promote CO2 hydrogenation conversion (Nature Catalysis, 2021, 4 (3): 242-250.). Therefore, silicon spheres are used as hard templates to disperse molybdenum disulfide, and surfactants are used as soft templates to intercalate between molybdenum disulfide layers to promote the production of monolayer molybdenum disulfide. Summary of the invention
[0005] The present invention adopts a combination of silicon dioxide and surfactant dual templates, and uses hydrazine hydrate reduction to prepare a monolayer molybdenum disulfide catalyst under normal pressure. Compared with the traditional chemical vapor deposition preparation strategy of monolayer molybdenum disulfide, the monolayer molybdenum disulfide prepared by the present invention has higher thermal stability and can maintain structural stability in a test at 600oC. Compared with bulk molybdenum disulfide prepared by the traditional hydrothermal method, the material produced by this preparation method has a higher specific surface area, more active sites exposed, and exhibits higher reverse water gas shift reaction activity.
[0006] The object of the present invention is to provide a method for synthesizing a monolayer molybdenum disulfide catalyst under normal pressure, which has the characteristics of high activity and high stability for high-temperature reverse water-gas shift reaction. The method has the characteristics of simple operation, strong repeatability and high universality.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme: a high-activity and high-stability monolayer molybdenum disulfide catalyst for high-temperature reverse water-gas shift reaction, using 30 to 100 silicon balls as hard templates, surfactants as soft templates, and using hydrazine hydrate reduction to achieve the preparation of monolayer molybdenum disulfide at normal pressure, the interlayer spacing of the obtained molybdenum disulfide is greater than 0.7nm, and the number of layers is mainly monolayer. By changing the amount of surfactant used, a series of catalysts can be obtained and recorded as SL-MoS2-X, where X represents the amount of surfactant used.
[0008] According to one aspect of the present application, a method for preparing a monolayer molybdenum disulfide catalyst is provided, comprising the following steps:
[0009] Silicon disulfide, water, a surfactant, ammonium sulfide and a molybdenum precursor are mixed, the pH is adjusted to 1 to 2 with a pH adjuster, reacted, hydrazine hydrate is added, refluxed, washed, separated, vacuum dried, and roasted to obtain a black solid;
[0010] The black solid is mixed with a sodium hydroxide solution, stirred, washed, separated, dried, and reduced and activated to obtain the monolayer molybdenum disulfide catalyst.
[0011] The size of the silicon disulfide is 30 to 100 nm;
[0012] The surfactant is selected from at least one of cetyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium bromide (DTAB), and polyvinylpyrrolidone (PVP);
[0013] The molybdenum precursor is selected from ammonium molybdate (NH4)6Mo7O 24 ·4H2O), molybdenum trioxide (MoO3), sodium molybdate (Na2MoO4·2H2O), and molybdic acid (H2MoO4).
[0014] The concentration of the hydrazine hydrate is 80 wt %.
[0015] The usage ratio of silicon disulfide, water, surfactant, ammonium sulfide, molybdenum precursor and hydrazine hydrate is: 5-10g: 100ml: 0.25-1g: 28-140mmol: 1-5mmol: 5-10ml;
[0016] Optionally, the molar ratio of ammonium sulfide to molybdenum precursor is greater than 28.
[0017] The reaction temperature is 40-60°C;
[0018] The reaction time is 2 to 4 hours;
[0019] The reflux temperature is 70-90°C;
[0020] The reflux time is 4 to 10 hours;
[0021] The vacuum drying temperature is 60-80°C;
[0022] The vacuum drying time is 6 to 10 hours;
[0023] The calcination temperature is 500-800°C;
[0024] The calcination time is 3 to 5 hours;
[0025] The heating rate of the calcination is 5-10°C / min.
[0026] The concentration of the sodium hydroxide solution is 2-5 mol / L.
[0027] The solid-liquid ratio of the black solid to the sodium hydroxide solution is 10-20 g: 200-500 ml.
[0028] The stirring temperature is 60-80°C;
[0029] The stirring time is 6 to 10 hours;
[0030] The drying temperature is 60-100°C;
[0031] The drying time is 6 to 12 hours.
[0032] The reduction activation comprises the following process:
[0033] The temperature is raised to the target temperature in an inert gas atmosphere, then switched to a hydrogen-containing atmosphere for 2 to 6 hours, and then lowered to room temperature in an inert gas atmosphere;
[0034] The inert gas atmosphere is selected from a nitrogen atmosphere and / or an inert gas atmosphere;
[0035] The target temperature is 400-600°C;
[0036] Optionally, the target temperature is 500-600°C.
[0037] Optionally, the specific steps are:
[0038] 1) Take 5-10g of hydrophilic silicon disulfide with a particle size of 30-100nm as a template, disperse it in 100mL of deionized water, and ultrasonicate it for 10-30min, add 0.25-1.0g of surfactant to the dispersion, adjust the pH of the solution with hydrochloric acid after it is fully dissolved, usually controlled at pH=1-2, add 28-140mmol of ammonium sulfide and 1-5mmol of molybdenum precursor to the solution in sequence, ensure that the molar ratio of ammonium sulfide to molybdenum precursor is greater than 28, transfer the mixture to a three-necked round-bottom flask, react in a water bath at 40°C for 2h, until the mixture completely turns dark red; then raise the water bath temperature to 70-90°C, add 5-10mL of 80% hydrazine hydrate solution to the formed mixture, react under condensation reflux conditions for 4-10h, until the mixture turns dark brown, the reaction is completed, wash it with deionized water and ethanol alternately three times, collect the solid by suction filtration, and vacuum dry it at 60°C;
[0039] 2) The dried solid was calcined in a tube furnace under argon atmosphere at 500-800°C for 3-5h, with a heating rate of 5°C min -1After the temperature drops to room temperature, collect the black solid, take 10-20 g of the calcined sample and disperse it in 200-500 mL of 2-5 mol L -1 In sodium hydroxide solution, the fully mixed suspension was stirred in a water bath at 60-80°C overnight, and the solid after reaction was collected by suction filtration, and fully washed with deionized water until the filtrate was close to neutral to remove the residual sodium ions on the surface, and the solid obtained by suction filtration was dried in a vacuum oven at 60°C for 12 hours. The obtained black solid is a monolayer molybdenum disulfide catalyst;
[0040] 3) The obtained monolayer molybdenum disulfide catalyst is subjected to reduction activation treatment, and the catalyst is placed in a tubular furnace for thermochemical reduction. First, the temperature is programmed to the target temperature under an argon atmosphere, and then switched to a reducing atmosphere for reduction. The treatment time is 2 to 6 hours, and then the temperature is lowered to room temperature in an inert atmosphere to obtain a reduced monolayer molybdenum disulfide catalyst.
[0041] According to another aspect of the present application, a single-layer molybdenum disulfide catalyst prepared by the above-mentioned preparation method is provided, wherein the interlayer spacing of the molybdenum disulfide is greater than 0.7 nm, and the number of layers is mainly single-layered.
[0042] According to another aspect of the present application, there is provided an application of the above-mentioned single-layer molybdenum disulfide catalyst for reverse water gas shift reaction.
[0043] A quartz tube fixed bed reactor is used, the particle size of the catalyst is 40-60 mesh, and the reaction evaluation is carried out after pretreatment in a reducing atmosphere. The reducing atmosphere is high-purity H2, the reduction temperature is 500°C, the reaction temperature is 300-600°C, preferably 500-600°C; the reaction pressure is 0.1MPa; the molar ratio of H2 to CO2 in the raw gas is 2-4, preferably 3-4; the gas space velocity is 5000-50000mL g -1 h -1 , preferably 30000mL g -1 h -1 .
[0044] The reduced SL-MoS2 catalyst is used for the reverse water-gas shift reaction, showing excellent high-temperature activity and stability, and the selectivity of CO in the product is maintained at more than 99%. In the catalyst described in the present invention, molybdenum disulfide is mainly a single-layer structure with an interlayer spacing greater than 0.7nm, and has excellent reverse water-gas shift activity and stability.
[0045] The beneficial effects of this application include:
[0046] The catalyst preparation method provided by the present invention is simple to operate, reliable, and conducive to large-scale production and use. The catalyst provided by the present invention prepares a monolayer of molybdenum disulfide by dispersing silicon balls combined with surfactant intercalation, which has a large specific surface area and a large amount of active site exposure, thereby significantly improving the activity and stability of the catalyst. The catalyst provided by the present invention is used for the reverse water-gas shift reaction, and the selectivity of CO in the product is maintained at more than 99%, and the reaction temperature distribution is wide, which is particularly suitable for use in high-temperature reverse water-gas shift reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a graph for evaluating the reaction performance of the catalyst in Example 1.
[0048] Figure 2 This is a reaction performance evaluation diagram of the catalyst in Comparative Example 1.
[0049] Figure 3 The stability diagram of the monolayer molybdenum disulfide catalyst in Example 2. Reaction conditions: 600°C, 0.1 MPa, GHSV = 54000 ml g -1 h -1 ;
[0050] Figure 4 This is a transmission electron microscope image of a single layer of molybdenum disulfide in Example 1, with a scale of 20 nm.
[0051] Figure 5 This is a transmission electron microscope image of a single layer of molybdenum disulfide in Example 3, with a scale of 20 nm.
[0052] Figure 6 This is a transmission electron microscope image of the multilayer molybdenum disulfide in Comparative Example 1, with a scale of 20 nm.
[0053] Figure 7 This is an atomic force microscope image of a single layer of molybdenum disulfide in Example 1.
[0054] Figure 8 This is an atomic force microscope image of the multilayer molybdenum disulfide in Comparative Example 1. DETAILED DESCRIPTION
[0055] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0056] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0057] Example 1
[0058] Take 10g of hydrophilic silica spheres with a particle size of 30nm, disperse them in 100mL of deionized water, and ultrasonicate them for 30min. Then, add 1.0g of CTAB to the dispersion and stir thoroughly to dissolve. Use HCl to adjust the solution pH to 1. Then, add 140mmol (NH4)2S and 5mmol (NH4)6Mo7O in sequence. 24 ·4H2O. Transfer the mixture to a three-necked round-bottom flask and react in a 40℃ water bath for 2h until the mixture completely turns dark red. Raise the water bath temperature to 90℃, add 10mL 80% N2H4·H2O solution to the mixture, and react under condensation reflux for 10h until the mixture turns dark brown. Wash alternately with deionized water and ethanol for 3 times, collect the solid by suction, and vacuum dry at 60oC.
[0059] The dried solid was calcined in a tubular furnace at 800°C for 5h under an Ar atmosphere, with a heating rate of 5°C / min. After cooling to room temperature, 20g of the calcined sample was taken, dispersed in 500mL of 5mol / L NaOH solution, and stirred overnight in an 80°C water bath. The solid after the reaction was collected by suction filtration, thoroughly washed with deionized water until the filtrate was close to neutral, and vacuum dried at 60°C for 12h to obtain a black single-layer MoS2 catalyst. The obtained single-layer MoS2 catalyst was placed in a tubular furnace, programmed to 600°C under an Ar atmosphere, and switched to a 5% H2 / Ar mixed atmosphere for reduction treatment for 5h. It was then cooled to room temperature under an inert atmosphere, and the reduced single-layer MoS2 catalyst was collected.
[0060] Example 2
[0061] Take 5g of hydrophilic silica spheres with a particle size of 100nm, disperse them in 100mL of deionized water, and ultrasonically treat them for 10min. Subsequently, add 0.25g of PVP to the dispersion, stir thoroughly to dissolve, and use HCl to adjust the pH of the solution to 2. Then, add 28mmol (NH4)2S and 1mmol Na2MoO4·2H2O in sequence. Transfer the mixed solution to a three-necked round-bottom flask and react in a 40℃ water bath for 2h until the mixture completely turns dark red. Raise the water bath temperature to 70℃, add 5mL of 80% N2H4·H2O solution to the mixture, and react under condensation reflux conditions for 4h until the mixture turns dark brown. Wash alternately with deionized water and ethanol 3 times, collect the solid by suction, and vacuum dry at 60℃.
[0062] The dried solid was calcined in a tubular furnace at 500°C for 3h under an Ar atmosphere, with a heating rate of 5°C / min. After cooling to room temperature, 10g of the calcined sample was dispersed in 200mL of 2mol / L NaOH solution, and stirred overnight in a 60°C water bath. The solid after the reaction was collected by suction filtration, thoroughly washed with deionized water until the filtrate was close to neutral, and vacuum dried at 60°C for 12h to obtain a black single-layer MoS2 catalyst. The obtained single-layer MoS2 catalyst was placed in a tubular furnace, programmed to 400°C under an Ar atmosphere, and switched to a high-purity H2 atmosphere for reduction treatment for 2h. It was then cooled to room temperature under an inert atmosphere, and the reduced single-layer MoS2 catalyst was collected.
[0063] Example 3
[0064] Take 8g of hydrophilic silica spheres with a particle size of 80nm, disperse them in 100mL of deionized water, and ultrasonically treat them for 15min. Subsequently, add 0.8g of DTAB to the dispersion, stir and dissolve thoroughly, and adjust the pH of the solution to 2 with HCl. Then, add 56mmol (NH4)2S and 2mmol H2MoO4 in sequence, transfer the mixed solution to a three-necked round-bottom flask, and react in a 40℃ water bath for 2h until the mixture completely turns dark red. Raise the water bath temperature to 85℃, add 8mL of 80% N2H4·H2O solution to the mixture, and react under condensation reflux conditions for 6h until the mixture turns dark brown. Wash alternately with deionized water and ethanol 3 times, collect the solid by suction, and vacuum dry at 60℃.
[0065] The dried solid was calcined in a tubular furnace at 700°C for 4 hours under an Ar atmosphere, with a heating rate of 5°C / min. After cooling to room temperature, 15g of the calcined sample was taken, dispersed in 400mL of 4mol / L NaOH solution, and stirred overnight in a 75°C water bath. The solid after the reaction was collected by suction filtration, thoroughly washed with deionized water until the filtrate was close to neutral, and vacuum dried at 60°C for 12 hours to obtain a black single-layer MoS catalyst. The obtained single-layer MoS2 catalyst was placed in a tubular furnace, programmed to 500°C under an Ar atmosphere, and switched to a 10% H2 / Ar mixed atmosphere for reduction treatment for 4 hours. It was then cooled to room temperature under an inert atmosphere, and the reduced single-layer MoS2 catalyst was collected.
[0066] Example 4
[0067] Take 8g of hydrophilic silica spheres with a particle size of 100nm, disperse them in 100mL of deionized water, and ultrasonically treat them for 10min. Subsequently, add 0.5g of PVP to the dispersion, stir and dissolve thoroughly, and use HCl to adjust the pH of the solution to 2. Then, add 32mmol (NH4)2S and 1.2mmol MoO3 in sequence. Transfer the mixed solution to a three-necked round-bottom flask and react in a 50℃ water bath for 3h until the mixture completely turns dark red. Raise the water bath temperature to 80℃, add 6mL of 80% N2H4·H2O solution to the mixture, and react under condensation reflux conditions for 5h until the mixture turns dark brown. Wash alternately with deionized water and ethanol 3 times, collect the solid by suction, and vacuum dry at 60℃.
[0068] The dried solid was calcined in a tubular furnace at 600°C for 4 hours under an Ar atmosphere, with a heating rate of 10°C / min. After cooling to room temperature, 10g of the calcined sample was taken, dispersed in 200mL 3mol / L NaOH solution, and stirred overnight in a 70°C water bath. The solid after the reaction was collected by suction filtration, thoroughly washed with deionized water until the filtrate was close to neutral, and vacuum dried at 60°C for 12 hours to obtain a black single-layer MoS2 catalyst. The obtained single-layer MoS2 catalyst was placed in a tubular furnace, programmed to 500°C under an Ar atmosphere, and switched to a high-purity H2 atmosphere for reduction treatment for 2 hours. It was then cooled to room temperature under an inert atmosphere, and the reduced single-layer MoS2 catalyst was collected.
[0069] Comparative Example 1
[0070] Take 6g of hydrophilic silica spheres with a particle size of 40nm, disperse them in 100mL of deionized water, and treat them with ultrasound for 25min. Adjust the pH of the solution to 1 with HCl. Then, add 112mmol (NH4)2 S and 4mmol MoO3, transfer the mixture to a three-necked round-bottom flask, and react in a 40℃ water bath for 2h until the mixture completely turns dark red. Raise the water bath temperature to 80℃, add 7mL 80% N2H4·H2O solution to the mixture, and react under condensation reflux for 8h until the mixture turns dark brown. Wash alternately with deionized water and ethanol 3 times, collect the solid by suction filtration, and vacuum dry at 60℃.
[0071] The dried solid was calcined in a tubular furnace at 600°C for 3h under an Ar atmosphere, with a heating rate of 5°C / min. After cooling to room temperature, 12g of the calcined sample was taken, dispersed in 300mL of 3mol / L NaOH solution, and stirred overnight in a 70°C water bath. The solid after the reaction was collected by suction filtration, thoroughly washed with deionized water until the filtrate was close to neutral, and vacuum dried at 60°C for 12h to obtain a black single-layer MoS2 catalyst. The obtained single-layer MoS2 catalyst was placed in a tubular furnace, programmed to 550°C under an Ar atmosphere, and switched to a 20% H2 / Ar mixed atmosphere for reduction treatment for 5h. It was then cooled to room temperature under an inert atmosphere, and the reduced multilayer MoS2 catalyst was collected.
[0072] Catalyst performance test
[0073] 0.2 g of the catalysts prepared in Examples 1 to 3 and Comparative Example 1 were respectively loaded into a quartz tube fixed bed reactor to evaluate the catalytic performance of the reverse water-gas shift reaction. First, H2 reduction treatment was performed at a temperature of 600°C and a pressure of normal pressure. The reverse water-gas shift reaction conditions were: reaction temperature 300-600°C, reaction pressure 0.1 MPa, synthesis gas volume space velocity 54000 ml / g -1 h -1 , the molar ratio of H2 to CO2 is 3. The raw gas and gas products were analyzed online using an Agilent 7890B gas chromatograph equipped with a TCD detector.
[0074] Figure 1 This is a graph for evaluating the reaction performance of the catalyst in Example 1.
[0075] Figure 2 This is a reaction performance evaluation diagram of the catalyst in Comparative Example 1.
[0076] Figure 3 The stability diagram of the monolayer molybdenum disulfide catalyst in Example 2. Reaction conditions: 600°C, 0.1 MPa, GHSV = 54000 ml g -1 h -1 ;
[0077] Figure 4 This is a transmission electron microscope image of a single layer of molybdenum disulfide in Example 1, with a scale of 20 nm.
[0078] Figure 5 This is a transmission electron microscope image of a single layer of molybdenum disulfide in Example 3, with a scale of 20 nm.
[0079] Figure 6 This is a transmission electron microscope image of the multilayer molybdenum disulfide in Comparative Example 1, with a scale of 20 nm.
[0080] Figure 7This is an atomic force microscope image of a single layer of molybdenum disulfide in Example 1.
[0081] Figure 8 This is an atomic force microscope image of the multilayer molybdenum disulfide in Comparative Example 1.
[0082] Depend on Figure 1 , 2 It can be seen that single-layer MoS2 has higher catalytic activity than multi-layer MoS2, and the activity in the high temperature zone is close to the equilibrium conversion rate, indicating a higher exposure of active sites.
[0083] Depend on Figure 3 It can be seen that the single-layer molybdenum disulfide catalyst has high stability and can maintain stability for more than 300 hours even under 600°C test conditions. In addition, CO is always the only product during the reaction, and the catalyst has high selectivity.
[0084] Depend on Figure 4 , 5 6 It can be seen that the single-layer MoS2 maintains a single-layer state, and the interplanar spacing is about 0.9nm, and the crystal structure is looser, while the average number of layers of multi-layer MoS2 remains at 4 to 5 layers, and the interplanar spacing is 0.6nm, which is in line with the standard MoS2 interplanar spacing, indicating that it has a better crystal structure.
[0085] Depend on Figure 7 , 8 It can be seen that the single-layer MoS2 does show a single-layer dispersed structure, while the multi-layer MoS2 has a larger number of layers.
[0086] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a monolayer molybdenum disulfide catalyst, characterized in that: The following steps are involved: Silicon disulfide, water, a surfactant, ammonium sulfide and a molybdenum precursor are mixed, the pH is adjusted to 1 to 2 with a pH adjuster, reacted, hydrazine hydrate is added, refluxed, washed, separated, vacuum dried, and roasted to obtain a black solid; The black solid is mixed with a sodium hydroxide solution, stirred, washed, separated, dried, and reduced and activated to obtain the monolayer molybdenum disulfide catalyst.
2. The preparation method according to claim 1, characterized in that: The size of the silicon disulfide is 30 to 100 nm; The surfactant is selected from at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide and polyvinylpyrrolidone; The molybdenum precursor is selected from at least one of ammonium molybdate, molybdenum trioxide, sodium molybdate and molybdic acid. The concentration of the hydrazine hydrate is 80 wt %.
3. The preparation method according to claim 1, characterized in that: The usage ratio of silicon disulfide, water, surfactant, ammonium sulfide, molybdenum precursor and hydrazine hydrate is: 5-10g: 100ml: 0.25-1g: 28-140mmol: 1-5mmol: 5-10ml; Preferably, the molar ratio of ammonium sulfide to molybdenum precursor is greater than 28.
4. The preparation method according to claim 1, characterized in that: The reaction temperature is 40-60°C; The reaction time is 2 to 4 hours; The reflux temperature is 70-90°C; The reflux time is 4 to 10 hours; The vacuum drying temperature is 60-80°C; The vacuum drying time is 6 to 10 hours; The calcination temperature is 500-800°C; The calcination time is 3 to 5 hours; The heating rate of the calcination is 5-10°C / min.
5. The preparation method according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 2-5 mol / L.
6. The preparation method according to claim 1, characterized in that: The solid-liquid ratio of the black solid to the sodium hydroxide solution is 10-20 g: 200-500 ml.
7. The preparation method according to claim 1, characterized in that: The stirring temperature is 60-80°C; The stirring time is 6 to 10 hours; The drying temperature is 60-100°C; The drying time is 6 to 12 hours.
8. The preparation method according to claim 1, characterized in that: The reduction activation comprises the following process: The temperature is raised to the target temperature in an inert gas atmosphere, then switched to a hydrogen-containing atmosphere for 2 to 6 hours, and then lowered to room temperature in an inert gas atmosphere; The inert gas atmosphere is selected from a nitrogen atmosphere and / or an inert gas atmosphere; The target temperature is 400-600°C; Preferably, the target temperature is 500-600°C.
9. A monolayer molybdenum disulfide catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The interlayer spacing of MoS2 is larger than 0.7nm, and the number of layers is mainly single layer.
10. Use of the monolayer molybdenum disulfide catalyst according to claim 9, characterized in that: Used for reverse water gas shift reaction.